Incidence and Association of Uveitis with COVID-19 Vaccination: A Systematic Review and Meta-Analysis - Bijaya K. Padhi (8087630) (2024)
Purpose In the wake of the COVID-19 pandemic, vaccines have been pivotal in curbing disease spread and severity. However, concerns over post-vaccination adverse events, including uveitis, an inflammatory ocular condition, have been noted. This systematic review and meta-analysis aimed to evaluate the incidence and association of uveitis following COVID-19 vaccination. Methods A literature search was performed across several databases on October 21, 2023. Human studies examining the incidence of uveitis post-COVID-19 vaccination were included. The Newcastle-Ottawa Scale was used for quality appraisal of the included studies. Meta-analysis was performed to assess the overall incidence of uveitis and the relative risk of developing the condition post-vaccination. All statistical analyses were performed using R software version 4.3. Results Six studies involving over 2 billion vaccine doses were included. The overall incidence of uveitis was 0.016% (95% CI: 0.010 to 0.026). No significant association was found between vaccination and the onset of uveitis (Relative Risk: 1.45 (95% CI: 0.82 to 2.57, p = 0.12) from four studies. The evidence quality was rated very low due to the limited number of studies and imprecision. Conclusion This analysis indicates a low incidence of uveitis following COVID-19 vaccination and no significant association with the vaccine. The findings are constrained by the small number of studies and low certainty of evidence, underscoring the need for further research. Comprehensive and longitudinal studies are necessary to confirm these findings and reinforce public confidence in COVID-19 vaccination programs. Other Information Published in: Ophthalmic Epidemiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09286586.2024.2343714